Delegation and Leader-Member Exchange: Main Effects, Moderators, and Measurement Issues - Schriesheim, Chester A.; Neider, Linda L.; Scandura, Terri A. (Academy of Management Journal, 1998)
Subordinate and supervisor leader-member exchange (LMX) were examined as correlates of delegation and as moderators of relationships between delegation and subordinate performance and satisfaction. Raw score analyses of data on 106 dyads showed both to be significantly related to delegation and to have similar main and moderating effects for subordinate performance and satisfaction. Finally, within- and between-groups analyses largely supported the level-of-analysis predictions of the LMX approach. Implications for future LMX research are discussed.